TRANSVERSAL (CROSS-SECTION) STUDY FOR REPRESENTATION OF IMPACTED MAXILLARY CANINES IN MACEDONIA - Stojanova, Liljana; Pavlovska, Irina; Taushanova, Biljana; Jankulovska, Mira; Bihorac, Elida (Journal of Morphological Sciences, 2018)
Background: The impacted maxillary canine can be defined as un-erupted teeth after its root development is complete. It can be detected in early stadium of development as early as 8 years. If there are signs of clinical presence of impaction, radiographic examination should be performed to confirm the diagnosis. Aim : The aim of this study is to determine occurrence of IMC in both genders and their aged features of appearance; to make classification depending on their localization and depending on their position according to the other anatomic structures in the alveolar bone; to find correlation between localization and both age groups, (10-15 and 15-69 years). Materials and methods : It is a cross-sectional survey carried out on 104 dental patients who attended representative policlinics and dental ordinations located in Skopje, Kumanovo and Kriva Palanka between 1.12.2017 and 28.02.2018. Their dental records were examined followed by panoramic radiographs. Thechi-squared test was used to examine potential differences in the distribution of impacted maxillary canines stratified by gender, age, location (left or right), and position. ð‘ƒ<0.05 was accepted as statistically significant. Results : The age group ranging from 10 to 19 years was the most prevalent and comprised 60.58% of all examinees with IMC. Out of all examinees, 81 (77.88%), had unilaterally impacted maxillary canines, while 23 (22.12%) had bilateral impactions. Dominant position of the IMC in younger group (up to 15 years), was mesioangular and vertical - 23 (47.92%), 20 (41.67%), consequently, and in the older group (from15 to 69 years) was mesioangular and horizontal position - 25 (44.64%), and 22 (39.29%), consequently (p-value 0.00025 sig). Conclusion : The early detection is crucial for successful treatment. Further demographic study is needed. Key words : impaction, impacted maxillary canine, panoramic, localization.